Manufacturing method for laminated coating structure and piston for internal combustion engine

By forming a pure metal layer on alloy members and then applying anodic oxidation or chemical conversion treatment, the method addresses the issue of uneven coatings caused by crystallization phases, resulting in improved surface smoothness and wear resistance for internal combustion engine pistons.

JP7647050B2Active Publication Date: 2025-03-18SUZUKI MOTOR CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020167803
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-02
Publication Date
2025-03-18
Estimated Expiration
2040-10-02

AI Technical Summary

Technical Problem

Existing methods for forming anodic oxide films or chemical conversion treatment films on alloy members, such as aluminum and magnesium alloys, are hindered by the crystallization phase present in these alloys, leading to uneven coatings and surface roughness, which negatively impact the performance and efficiency of internal combustion engine pistons.

Method used

A method involving the formation of a pure metal layer on the surface of the alloy member, followed by anodic oxidation or chemical conversion treatment, to create a film laminated structure with a smooth and uniform surface, unaffected by the crystallization phase.

Benefits of technology

The proposed method achieves a smooth film laminate structure that enhances the wear resistance and surface smoothness of piston components, reducing blow-by gas flow rates, suppressing oil rise, and maintaining mechanical properties at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647050000002
    Figure 0007647050000002
  • Figure 0007647050000003
    Figure 0007647050000003
  • Figure 0007647050000004
    Figure 0007647050000004
Patent Text Reader

Abstract

To provide a method for manufacturing a film laminate structure in which a smooth anodic oxide film or chemical conversion treatment film is formed on a surface of an alloy member without influenced by a crystallized phase contained in the alloy member, and a piston for an internal combustion engine.SOLUTION: A method for manufacturing a film laminate structure includes the steps of: forming a pure metal layer 95 on a surface 93 of an alloy member 90; and obtaining a film laminate structure including the alloy member and a film 94 formed on a surface of the alloy member by subjecting the pure metal layer to anodic oxide treatment or chemical conversion treatment. A piston for an internal combustion engine has a film laminate structure. In this film laminate structure, (b) an interface between the alloy member and the film is linear in a cross section of the film laminate structure, and (c) a crystallized phase exists in the interface, and the interface is linear in a cross section of the film laminate structure except a portion in which the crystallized phase exists.SELECTED DRAWING: Figure 13
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a coating stack structure and a piston for an internal combustion engine. [Background technology]

[0002] In recent years, there has been an increasing demand for more efficient engines, higher compression ratios, and supercharged engines in response to environmental regulations, and the maximum combustion pressure of engines is rising. Against this background, there has also been a strong demand for improved wear resistance of piston ring grooves (especially top ring grooves). One method known for improving the wear resistance of ring grooves is to form an anodized film. This is because an anodized film is more than twice as hard as the aluminum alloy piston material, and has excellent wear resistance.

[0003] However, aluminum alloys generally used as piston materials contain a lot of silicon to improve castability and wear resistance, and the silicon crystallizes into a metal structure. Since anodized films are formed by oxidizing aluminum, in areas where silicon crystallizes in large quantities (or in large shapes) on the surface of the part, the anodized film is difficult to form, resulting in an uneven film and worsening surface roughness.

[0004] This problem occurs not only in aluminum alloys, but also in alloy members such as magnesium alloys. In addition, since chemical conversion treatment is a process in which aluminum reacts with a chemical conversion treatment solution to form a film, similar to anodization, the chemical conversion treatment film is also affected by the crystallized phase contained in such alloy members, resulting in an uneven film and worsening surface roughness.

[0005] When the surface roughness of a piston surface film, such as an anodized film, deteriorates, the combustion gas sealing performance decreases, causing an increase in the flow rate of blow-by gas and a deterioration in fuel efficiency. In addition, when the surface roughness of the piston surface film deteriorates, a phenomenon occurs in which engine oil used to lubricate engine parts flows into the combustion chamber (hereinafter referred to as "oil rise"). When engine oil is burned in the combustion chamber, it causes the generation of substances subject to European environmental regulations, such as PM (Particulate Matter), and the increase in the number of PN (Particle Number), so the smoothness of the surface of the anodized film is required.

[0006] Patent Document 1 describes a method for anodizing the aluminum alloy part by repeating a step of applying a positive voltage to the aluminum alloy part and a step of removing the electric charge, with the current application time of the positive voltage being 25 μs to 100 μs, for the purpose of forming a uniformly thick and dense anodized film on the surface of the aluminum alloy part. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2006-83467 A Summary of the Invention [Problem to be solved by the invention]

[0008] In view of the above problems, the present invention has an object to provide a method for manufacturing a coating layer structure in which a smooth anodized coating or chemical conversion coating is formed on the surface of an alloy member without being affected by crystallized phases contained in the alloy member, and a piston for an internal combustion engine having the coating layer structure. [Means for solving the problem]

[0009] In order to achieve the above-mentioned object, one aspect of the present invention is a method for manufacturing a coating laminate structure, the method including the steps of forming a pure metal layer on a surface of an alloy component, and performing anodizing or chemical conversion treatment on the pure metal layer to obtain a coating laminate structure comprising the alloy component and a coating formed on its surface.

[0010] In another aspect, the present invention provides a piston for an internal combustion engine having a coating layer structure comprising an alloy member and a coating formed on a surface thereof, in which (a) an interface between the alloy member and the coating in the coating layer structure is linear in a cross section of the coating layer structure, or (b) a crystallized phase contained in the alloy member is present at the interface between the alloy member and the coating in the coating layer structure, and the interface is linear in a cross section of the coating layer structure except for a portion where the crystallized phase is present. Effect of the Invention

[0011] Thus, according to the present invention, it is possible to obtain a film laminate structure in which a smooth anodized film or chemical conversion film is formed on the surface of an alloy member without being affected by the crystallized phase contained in the alloy member. Also, by forming the surface of a piston for an internal combustion engine, particularly the surface of the first ring groove, into such a film laminate structure with a smooth surface, it is possible to reduce the flow rate of blow-by gas and also to suppress oil leakage. Furthermore, since the entire pure metal layer formed on the alloy member becomes a surface film by anodizing or chemical conversion, and no pure metal layer remains under this surface film, it is possible to prevent a decrease in mechanical properties (high-temperature fatigue strength, tensile strength, yield strength, etc.) at high temperatures. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a front view showing a schematic diagram of a piston for an internal combustion engine. [Diagram 2] FIG. 1 is a flow diagram showing an embodiment of a method for manufacturing a coating laminate structure according to the present invention. [Diagram 3]3 is a flow diagram showing in more detail the pure aluminum layer forming step in the method for producing the coating laminate structure shown in FIG. 2. [Figure 4] FIG. 4 is a schematic diagram illustrating an electron beam evaporation method, which is an example of carrying out the pure aluminum layer forming step shown in FIG. 3. [Diagram 5] FIG. 4 is a schematic diagram illustrating an electron beam evaporation method, which is an example of carrying out the pure aluminum layer forming step shown in FIG. 3. [Figure 6] FIG. 3 is a schematic diagram illustrating anodizing treatment as an example of carrying out a surface treatment step in the manufacturing method of the coating laminate structure shown in FIG. 2. [Figure 7] 1A and 1B are side views showing a schematic view of a pure aluminum layer before and after anodizing treatment. [Figure 8] 1 is a graph showing the change in voltage with respect to processing time when anodizing is performed by direct current electrolysis. [Figure 9] 1 is a graph showing a change in current with respect to treatment time when anodizing is performed by AC / DC superimposed electrolysis. [Figure 10] FIG. 3 is a schematic diagram illustrating a chemical conversion treatment as an example of carrying out a surface treatment step in the manufacturing method of the coating laminate structure shown in FIG. 2. [Figure 11] 1 is a side view showing a pure aluminum layer before and after a chemical conversion treatment is performed; FIG. [Figure 12] FIG. 1 is a cross-sectional view showing a schematic diagram of a coating laminate structure obtained by a conventional method. [Figure 13] FIG. 1 is a cross-sectional view showing a schematic diagram of a coating laminate structure obtained by the present invention. [Figure 14] 1 is an optical microscope photograph showing a cross section of a coating laminate structure obtained in an example and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of a method for manufacturing a film laminate structure and a piston for an internal combustion engine according to the present invention will be described with reference to the attached drawings. This embodiment is for manufacturing a piston for an internal combustion engine having a film laminate structure, but the manufacturing method of the present invention is not limited thereto and can also be applied to manufacturing alloy members on which an anodized film is formed other than a piston for an internal combustion engine. The drawings are drawn with a priority on ease of understanding and are not drawn to scale.

[0014] First, a piston for an internal combustion engine will be described. As shown in FIG. 1, a piston 10 for an internal combustion engine has three ring grooves formed on its outer circumferential surface, in order from the piston crown surface 11 side, namely, a first ring groove 13 (also called a top ring groove), a second ring groove 15, and an oil ring groove 17. On the outer circumferential surface, a portion between the piston crown surface 11 and the first ring groove 13 is called a first land 12, a portion between the first ring groove 13 and the second ring groove 15 is called a second land 14, a portion between the second ring groove 15 and the oil ring groove 17 is called a third land 16, and a portion beyond the oil ring groove 17 is called a skirt portion 18. A first ring (also called a top ring) (not shown) is fitted into the first ring groove 13, a second ring (not shown) is fitted into the second ring groove 15, and an oil ring (not shown) is fitted into the oil ring groove 17. Furthermore, the internal combustion engine piston 10 has a piston pin hole 19 in which a piston pin (not shown) slides.

[0015] The piston 10 for an internal combustion engine is formed of an alloy member such as an aluminum alloy or a magnesium alloy. These alloys are excellent in light weight, strength, mechanical properties (high temperature fatigue strength, tensile strength, proof stress, etc.), and heat resistance. The aluminum alloy contains silicon (Si) as a component that contributes to wear resistance and aluminum adhesion resistance. Examples of such aluminum alloys include AC materials such as AC4, AC8, AC8A, and AC9, ADC materials such as ADC10 to ADC14, and A4000, etc. for pistons. In addition, magnesium alloys contain aluminum and calcium for the purpose of heat resistance. Examples of such magnesium alloys include Mg-Al-Ca-based alloys such as ACM522. In the metal structure of such alloys, a crystallized phase of silicon or Ca-Al-based additives exists in the matrix, and it is considered that this crystallized phase prevents the formation of a smooth anodized film or chemical conversion coating. Therefore, in this embodiment, the case of an aluminum alloy will be described, but the present invention can be similarly applied to other alloys having a metal structure in which a crystallized phase exists.

[0016] The locations of the internal combustion engine piston 10 on which the coating laminate structure according to the present invention is formed include, for example, the piston crown surface 11, piston ring grooves 13, 15, 17, the skirt portion 18, and the piston pin hole 19. The coating laminate structure is formed on one or more of these locations.

[0017] The piston crown surface 11 is required to be smooth, and the lower the surface roughness, the better the flow in the combustion chamber (the easier it is to achieve the flow intended at the time of design). In particular, in a direct injection engine (a type of engine that injects fuel directly into the combustion chamber), the lower the surface roughness, the less fuel adheres to the piston and the better the fuel economy. The reduced surface area of ​​the piston crown surface 11 reduces cooling losses.

[0018] The piston ring grooves 13, 15, 17 are required to be smooth and wear-resistant. The lower the surface roughness, the better the adhesion with the piston ring, which reduces blow-by gas and oil leakage, improving fuel economy and complying with environmental regulations. The combustion gas is sealed off, suppressing the amount of blow-by gas and improving fuel economy. In particular, fuel economy is improved by suppressing heat escape below the first ring groove 13. This can also be said to reduce cooling loss. Wear resistance is effective for the part that adheres to the piston ring. It is particularly effective to make the upper and lower surfaces of the first ring groove have a film laminate structure.

[0019] The skirt portion 18 is required to have smoothness and wear resistance, and the lower the surface roughness, the better the sliding and initial fit with the cylinder bore (not shown). Wear resistance is effective for the sliding portion with the cylinder bore.

[0020] The piston pin hole 19 is required to have smoothness and wear resistance, and the lower the surface roughness, the lower the sliding resistance of the piston pin. Wear resistance is effective for the sliding portion of the piston pin.

[0021] Next, a manufacturing method of the piston for an internal combustion engine according to the present embodiment will be described. As shown in FIG. 2, the manufacturing method 20 of the piston for an internal combustion engine includes a step 21 of casting the piston, a step 22 of heat treating the cast piston, a step 23 of further processing the heat treated piston, a step 24 of forming a pure aluminum layer on the portion to be coated with a laminated film structure, and a step 25 of surface treating the pure aluminum layer. In the surface treatment step 25, a film is formed by anodizing or chemical conversion treatment. If necessary, the method may also include a step (not shown) of forming a resin coat on the film. The resin coat is a resin film with a low friction coefficient that is formed especially on the skirt portion 18, and has been commonly used in pistons for four-wheel vehicles in recent years.

[0022] The above-mentioned casting, heat treatment and machining steps 21, 22 and 23 are similar to the steps used in manufacturing a general piston for an internal combustion engine, and therefore a detailed explanation thereof will be omitted here.

[0023] 3, the pure aluminum layer forming step 24 further includes a step 31 of masking the portion to be formed, a step 32 of degreasing the portion exposed by the masking, a step 34 of washing the portion with water, a step 34 of drying the portion, a step 36 of forming a pure aluminum layer on the portion, and a step 37 of removing the masking. If necessary, a step 35 of activating the portion to be formed may be included between the drying step 34 and the step 36 of forming the pure aluminum layer.

[0024] In the masking step 31, the periphery of the target area is covered with a masking material so that the pure aluminum layer is not formed on areas other than the area where the anodized film is to be formed. For example, when forming a film on the piston crown surface 11 and the first ring groove 13, the first land 12 and the second land 14 are covered with the masking material. As the masking material, it is preferable to use a rubber material in consideration of productivity. The type of rubber that can be used may be natural rubber, butadiene rubber, styrene rubber, acrylic rubber, urethane rubber, nitrile rubber, silicone rubber, etc., but when anodizing is performed in the subsequent surface treatment step 25, it is more preferable to use nitrile rubber or silicone rubber that is resistant to the treatment solution such as sulfuric acid used in the anodizing process, because the anodizing process can be performed with the masking material attached.

[0025] After the masking step 31, a degreasing step 32, a water washing step 33, and a drying step 34 are performed in this order. These are similar to the processes generally performed to remove impurities from the film-forming target area, and therefore a detailed description thereof will be omitted here.

[0026] Then, a step 36 is performed in which a pure aluminum layer is formed on the film-forming target portion exposed from the masking material. When the internal combustion engine piston 10 is made of a magnesium alloy, a pure magnesium layer is formed. That is, a layer (pure metal layer) of only the metal that is the main component of the alloy to be formed is formed. For example, an electron beam evaporation method is used as the film-forming method. As shown in FIG. 4 and FIG. 5, an electron beam evaporation device 40 uses an electron gun 42 in a vacuum chamber 41 to heat and evaporate pure aluminum 43, which is an evaporation material 43, to generate material component particles 44, thereby forming a pure aluminum layer on the film-forming target portion of the internal combustion engine piston 10. The internal combustion engine piston 10 is fixed by a spigot jig 45 and rotatably installed in the vacuum chamber 41 by a support stand 47 equipped with a motor 46. The internal combustion engine piston 10 is covered with a masking material 48 from the second land to the skirt portion.

[0027] FIG. 4 shows a case where a pure aluminum layer is formed on the first ring groove 13 of the piston 10 for an internal combustion engine. The first ring groove 13 of the piston 10 for an internal combustion engine is arranged in a direction facing the evaporation material 43, and the piston 10 for an internal combustion engine is rotated along its central axis, so that a pure aluminum layer is formed on the inner surface of the first ring groove 13. FIG. 5 shows a case where a pure aluminum layer is formed on the piston crown surface 11 of the piston 10 for an internal combustion engine. The piston 10 for an internal combustion engine is arranged in a direction facing the evaporation material 43, and the piston 10 for an internal combustion engine is rotated along its central axis, so that a pure aluminum layer is formed on the surface of the piston crown surface 11. After the pure aluminum layer is formed, a step 37 of removing the masking is performed.

[0028] The method for forming the pure aluminum layer is not limited to the above-mentioned electron beam deposition method, and any vapor deposition method can be widely used. The vapor deposition method may be a chemical vapor deposition method (CVD method) or a physical vapor deposition method (PVD method) other than the above-mentioned electron beam deposition method. Before forming the pure aluminum layer, a step 35 may be performed in which the area to be formed is activated. The activation method may be a known activation method depending on the CVD method or PVD method used as the film formation method.

[0029] The pure aluminum layer thus formed is subjected to a surface treatment step 25. The surface treatment is anodizing or chemical conversion treatment. This results in a film laminate structure in which an anodized film or a chemical conversion treatment film is formed on the surface of the aluminum alloy.

[0030] The anodizing treatment is performed, for example, as shown in FIG. 6, by immersing an electrode plate such as titanium or carbon as a cathode 63 and a piston for an internal combustion engine as an anode 64 in an electrolytic solution 62 such as sulfuric acid or phosphoric acid in an electrolytic bath 61 in an anodizing treatment device 60, and by passing electricity from a power source 65, the surface of the piston for an internal combustion engine is oxidized. As a result, an anodized film 65 is formed on the surface of the piston for an internal combustion engine, which is the anode 64. The electrolytic method may be any of DC electrolysis, AC electrolysis, and AC / DC superimposed electrolysis, but in order to obtain a smoother film, it is more preferable to perform the treatment using AC / DC superimposed electrolysis. Note that FIG. 6 shows a case in which the entire piston for an internal combustion engine is immersed in the electrolytic solution 62 in the electrolytic bath 61, but the present invention is not limited to this, and it is sufficient that the part of the piston for an internal combustion engine to be film-formed is immersed in the electrolytic solution 62.

[0031] The relationship between the thickness of the anodized film thus obtained and the thickness of the pure aluminum layer before the surface treatment will be described with reference to FIG. 7. As described above, the anodized film is an aluminum oxide film. As shown in FIG. 7, the surface 52s of the anodized film 52 after the surface treatment rises in size by about half the thickness of the anodized film 52 relative to the treatment surface 51a of the pure aluminum layer 50a before the surface treatment. That is, the surface 51b (interface with the anodized film 52) of the pure aluminum layer 50a after the surface treatment drops by about half the thickness of the anodized film 52. Therefore, in order to turn the entire pure aluminum layer 50a into the anodized film 52 by performing the anodization treatment, the thickness of the pure aluminum layer 50a is set to half or less of the thickness of the anodized film 52 to be formed.

[0032] For example, if the thickness of the anodized coating 52 is desired to be 20 μm, then if the pure aluminum layer 50a is formed to a thickness of 10 μm or less, the entire pure aluminum layer 50a can be turned into the anodized coating 52 by anodizing. From the viewpoint of wear resistance, the thickness of the anodized coating is preferably in the range of 1 to 60 μm, and more preferably in the range of 5 to 30 μm. Accordingly, the thickness of the pure aluminum layer is preferably in the range of 0.5 to 30 μm, and more preferably in the range of 2.5 to 15 μm.

[0033] Next, a method for turning the entire pure aluminum layer into an anodized film will be described. The method differs between DC electrolysis and AC / DC superimposed electrolysis. DC electrolysis is performed by current control, while AC / DC superimposed electrolysis is performed by voltage control. The method will be described in detail below.

[0034] In DC electrolysis, as shown in the graph of FIG. 8, as the time of anodization passes, the resistance value increases due to the growth of the anodized film, so that in section 81, where the anodized film is formed by reaction with the pure aluminum layer, the voltage rises at a constant rate when the current is passed at a constant rate. Then, from the point 82 when the anodized film reaches the aluminum alloy, which is the base material under the pure aluminum layer, the voltage rises sharply due to insulators such as silicon in the base material. In section 83, where the anodized film is formed by reaction with the aluminum alloy layer, the rate of voltage rise is thus higher than that of section 81. Therefore, in anodization by DC electrolysis, if the current is passed at a constant rate and the voltage is measured, and the anodization is terminated when the rate of voltage rise increases, it is possible to control so that the entire pure aluminum layer becomes an anodized film. Note that the anodization may be continued even after the rate of voltage rise increases.

[0035] In AC / DC superimposed electrolysis, as shown in the graph of FIG. 9, as the time of anodizing process elapses, the resistance value increases due to the growth of the anodized film, so that in section 86 where the anodized film is formed by reaction with the pure aluminum layer, when the voltage is kept constant, the current drops at a constant rate. Then, from the point 87 where the anodized film reaches the aluminum alloy, which is the base material under the pure aluminum layer, the current drops sharply due to insulators such as silicon in the base material. In section 88 where the anodized film is formed by reaction with the aluminum alloy layer, the drop rate of the current is thus higher than that of section 86. Therefore, in anodizing process using AC / DC superimposed electrolysis, the voltage is kept constant, the current is measured, and the anodizing process is terminated when the drop rate of the current increases, so that the entire pure aluminum layer can be controlled to become an anodized film. Note that the anodizing process may be continued even after the drop rate of the current has increased.

[0036] For example, when a chemical conversion treatment device 70 is used as shown in FIG. 10, the chemical conversion treatment is performed by immersing an internal combustion engine piston, which is an object to be treated 73, in a chemical conversion treatment liquid 72 in a treatment tank 71 and causing a chemical reaction. As a result, the surface of the object to be treated 73 is changed into a chemical conversion coating, and a coating 74 is formed by a compound derived from the material of the object to be treated 73. For example, in the case of zinc phosphate treatment, the chemical conversion treatment liquid 72 may be a solution containing phosphate ions and zinc ions as main components. Note that FIG. 10 shows a case where the entire internal combustion engine piston is immersed in the chemical conversion treatment liquid 72 in the treatment tank 71, but the present invention is not limited to this, and it is sufficient that the film formation target portion of the internal combustion engine piston is immersed in the chemical conversion treatment liquid 72. Furthermore, the chemical conversion treatment is not limited to such an immersion method, and for example, a chemical conversion treatment coating can be formed on the surface by spraying the chemical conversion treatment liquid on the object to be treated.

[0037] Chemical conversion coating generally involves the steps of degreasing, surface conditioning (to precipitate fine crystal particles), chemical conversion coating (main treatment), and cleaning, in that order. Fine crystal grains of about a few μm are precipitated on the surface of the chemical conversion coating, but if degreasing is insufficient, if surface conditioning is not performed, or if the chemical conversion coating solution deteriorates, the precipitated crystal grains will become coarse, resulting in a worsening of surface roughness. To obtain a smoother coating, it is desirable to properly manage the degreasing and chemical conversion coating processes, and to introduce a surface conditioning process.

[0038] The relationship between the thickness of the chemical conversion coating thus obtained and the thickness of the pure aluminum layer before the surface treatment will be described with reference to FIG. 11. In the chemical conversion treatment, ions necessary for the growth of the coating (for example, phosphate ions and zinc ions in a zinc phosphate coating) are mainly supplied from the chemical conversion solution. Therefore, as shown in FIG. 11, the thickness of the chemical conversion coating is such that the surface 53s of the chemical conversion coating 53 after the surface treatment rises in dimension by more than 1 / 2 the thickness of the chemical conversion coating 53, relative to the treatment surface 51a of the pure aluminum layer 50a before the surface treatment. In other words, the surface 51c (interface with the chemical conversion coating 53) of the pure aluminum layer 50a after the surface treatment drops by less than 1 / 2 the thickness of the chemical conversion coating 53. Therefore, in order to turn the entire pure aluminum layer 50a into the chemical conversion coating 53 by performing the chemical conversion treatment, the thickness of the pure aluminum layer 50a is set to be less than half the thickness of the anodized coating 52 to be formed.

[0039] For example, when the thickness of the chemical conversion coating 53 is desired to be 20 μm, if the pure aluminum layer 50a is formed to a thickness of less than 10 μm, the entire pure aluminum layer 50a can be turned into the chemical conversion coating 53 by performing chemical conversion treatment. The degree of increase in the film thickness varies depending on the type of chemical conversion treatment solution used. From the viewpoint of abrasion resistance, the film thickness of the chemical conversion coating is preferably in the range of 1 to 20 μm, and more preferably in the range of 5 to 15 μm. Accordingly, the film thickness of the pure aluminum layer is preferably in the range of less than 0.5 μm to less than 10 μm, and more preferably in the range of less than 2.5 μm to less than 7.5 μm.

[0040] Next, a method for converting the entire pure aluminum layer into a chemical conversion coating will be described. As described above, the chemical conversion treatment changes the surface of the product to be treated into a chemical conversion coating, so the time for the entire pure aluminum layer to react with the chemical conversion solution can be calculated in advance. Therefore, if the chemical conversion treatment is terminated at the time when the reaction with the pure aluminum layer is completed, the entire pure aluminum layer can be converted into a chemical conversion coating. The chemical conversion treatment may be continued even after the predetermined time has elapsed.

[0041] Furthermore, the difference in the film laminate structure obtained when a conventional aluminum alloy is surface-treated and when a pure aluminum layer is formed on the aluminum alloy of the present invention and then the surface treatment is performed will be described with reference to Figures 12 and 13. Note that the following description is for the case where anodizing is performed as the surface treatment, but the same is basically true for chemical conversion treatment.

[0042] In the conventional method, as shown in Fig. 12, anodization of an aluminum alloy 90 is likely to cause unevenness on the surface of an anodized film 94a obtained by anodization due to the influence of crystallized phases such as silicon in a matrix 91. On the other hand, in the present invention, as shown in Fig. 13, a pure aluminum layer 95 is formed on a surface 93 of an aluminum alloy 90, and since there is no crystallized phase such as silicon in the pure aluminum layer 95, unevenness does not occur on the surface of anodized films 94b, 94c obtained by anodization, and very smooth anodized films 94b, 94c can be obtained.

[0043] In the present invention, two types of anodized films 94b and 94c can be obtained. One is a case where only the pure aluminum layer 95 is anodized to change it into anodized film 94b, and as shown in Fig. 13(b), this anodized film 94b does not contain a crystallized phase such as silicon (hereinafter referred to as a "crystallized-phase-free anodized film"). The other is a case where the pure aluminum layer 95 and even a part (surface layer region) of the aluminum alloy thereunder are anodized to change it into anodized film 94c, and as shown in Fig. 13(c), this anodized film 94c has a structure in which the surface layer does not contain a crystallized phase such as silicon, but the deeper layer contains a crystallized phase (hereinafter referred to as a "crystallized-phase-containing anodized film").

[0044] The crystallized-phase-containing anodic oxide coating 94c has a continuous coating structure due to the fact that both the portion that was the pure aluminum layer 95 and the portion that was the aluminum alloy 90 are changed into an anodic oxide coating, and is strongly adhered to the aluminum alloy 90, so that the crystallized-phase-containing anodic oxide coating 94c can obtain high durability. The thickness of the deep portion containing the crystallized phase in the crystallized-phase-containing anodic oxide coating 94c is preferably half or less of the entire coating. This is because, although it depends on the size of the crystallized phase 92 in the aluminum alloy 90, as described above, the anodic oxide coating is formed in such a way that the dimensions increase in the surface direction, and therefore, if the proportion of the deep portion containing the crystallized phase increases, the adverse effect on the smoothness of the anodic oxide coating 94c increases.

[0045] In addition, as a difference between the film laminate structure obtained by the conventional method and the present invention, when the aluminum alloy is surface-treated by the conventional method, the interface 93a between the aluminum alloy 90 and the anodized film 94a in the cross section of the film laminate structure is uneven due to the influence of the crystallized phase 92 of silicon or the like in the aluminum alloy 90, as shown in FIG. 12(b). On the other hand, in the present invention, as shown in FIG. 13(b), since the pure aluminum layer 95 does not have a crystallized phase, the interface 93b between the aluminum alloy 90 and the crystallized-phase-free anodized film 94b in the cross section of the film laminate structure is linear. In addition, as shown in FIG. 13(c), in the case of the crystallized-phase-containing anodized film 94c, the interface 93c between the aluminum alloy 90 and the crystallized-phase-containing anodized film 94c in the cross section of the film laminate structure has the crystallized phase 92, but the interface 93c is linear except for the part where the crystallized phase 92 is present.

[0046] The film laminated structure of the present embodiment thus obtained has a uniform film thickness, is dense and hard, and has a smooth surface. In particular, the surface roughness Ra of the anodized film or the chemical conversion coating is preferably 1.3 μm or less, more preferably 1.0 μm or less. The surface roughness index Ra represents the arithmetic mean roughness of the contour curve, as specified by JIS B0601. By smoothing the surface of the piston 10 for an internal combustion engine, particularly the surface of the first ring groove 13, in this manner, the airtightness between the first ring groove 13 and the first ring (not shown) can be made very high, and the flow rate of blow-by gas leaking from the combustion chamber to the crank chamber through the gap between the piston 10 for an internal combustion engine and the cylinder (not shown) can be reduced. In addition, oil leakage can be suppressed, and therefore PM and PN can be suppressed within the required values.

[0047] Furthermore, the entire pure aluminum layer 95 formed on the aluminum alloy 90 is turned into an anodized film 94 or a chemical conversion film by anodizing or chemical conversion treatment, and no pure aluminum layer remains under these films, so that deterioration of mechanical properties (high-temperature fatigue strength, tensile strength, yield strength, etc.) at high temperatures can be prevented. EXAMPLES

[0048] Examples and comparative examples of the present invention will be described below.

[0049] [Example] A test piece of A1100 material (aluminum purity 99% or more) was prepared to simulate a pure aluminum layer formed on an aluminum alloy member. The surface of the test piece was polished in advance to make the surface roughness equivalent to the roughness of the piston ring groove surface (Ra: 0.05 to 0.1 μm). The surface was then anodized. Sulfuric acid (5°C) was used as the electrolyte, and a titanium plate was attached to the cathode and the test piece to the anode to perform the anodization.

[0050] Two types of electrolysis were performed: direct current electrolysis and AC / DC superimposed electrolysis. The treatment time for each was 1 minute, and an anodic oxide film was formed on the test piece. The electrolysis conditions were: direct current electrolysis, current density 12 A / dm 2 For AC / DC superimposed electrolysis, constant voltage electrolysis was performed at a positive voltage of 30 V, a negative voltage of -2 V, and a frequency of 12 kHz.

[0051] The anodized films were evaluated for surface roughness, film thickness, and film hardness. Surface roughness was measured in accordance with JIS B 0601-2001, with the arithmetic mean roughness Ra measured at a measurement length of 4 mm and a cutoff of 0.8 mm. Film thickness was measured by cutting the test piece and examining the cross section of the film using an optical microscope. Film hardness was measured using a micro Vickers hardness tester on the cross section of the anodized film.

[0052] [Comparative Example] Anodizing treatment was performed on test pieces made of aluminum alloy AC8A containing 10% or more silicon. The test pieces of the comparative examples were polished to the same roughness as the piston ring groove surface as in the examples. The anodizing treatment was performed using only AC / DC superimposed electrolysis. An anodized film was formed on the test pieces under the same conditions as in the examples, except that the treatment time was 40 seconds. The anodized film thus formed was evaluated in the same manner as in the examples.

[0053] The evaluation results of the anodized films produced in the examples and comparative examples are shown in Table 1. Optical microscope photographs showing the cross sections of the anodized films produced in the examples and comparative examples are shown in Fig. 14. In Fig. 14, reference numeral 96 denotes an embedding resin for observing the cross section, and the surface of the anodized film 94 is indicated by a dashed line.

[0054] [Table 1]

[0055] As shown in Table 1, in the examples, an anodized film having a thickness of about 10 μm was obtained by both DC electrolysis and AC / DC superimposed electrolysis. Although the hardness differed slightly depending on the type of electrolysis, both had a Vickers hardness of 400 HV or more, which was sufficient for the purpose of imparting wear resistance to the piston. In addition, as shown in FIG. 14, the surface roughness Ra of the surface of the anodized film 94 formed on the pure aluminum test piece 90 was 0.57 μm by DC electrolysis and 0.22 μm by AC / DC superimposed electrolysis, and an anodized film with a very smooth surface texture was produced, especially by AC / DC superimposed electrolysis.

[0056] On the other hand, in the comparative example, an anodized film having a thickness of about 10 μm and a Vickers hardness of 393 HV was obtained, which was almost the same as that of the example, but the surface roughness Ra was 1.35 μm, which was significantly larger than that of the example. This is presumably because the surface of the anodized film 94 became uneven due to the influence of a crystallized phase such as silicon in the aluminum alloy 92, as shown in FIG. [Explanation of symbols]

[0057] 10. Pistons for internal combustion engines 11 Piston crown surface 12 Round 1 13 First ring groove 14 Land 2 15 Second ring groove 16 Third Land 17 Oil ring groove 18 Skirt Club 19 Piston pin hole 20. Manufacturing method for film laminate structure 40 Electron beam deposition equipment 41 Vacuum chamber 42 Electron Gun 43 Evaporation Material 44 Material component particles 45 Inlay jig 46 Motor 47 Support stand 48 Masking material 50 pure aluminum layers 52 Anodized film 53 Chemical conversion coating 60 Anodizing Equipment 70 Chemical treatment equipment 90 Aluminum alloy 91 Matrix 92 Crystallized phase 94 Anodized film 95 Pure Aluminum Layer 96 Embedding Resin

Claims

1. A method for manufacturing a coating laminate structure comprising the steps of: forming a pure metal layer of aluminum in the case of an aluminum alloy or magnesium in the case of a magnesium alloy containing aluminum and calcium on a surface of an alloy member, the pure metal layer being aluminum in the case of an aluminum alloy or magnesium in the case of the magnesium alloy; and performing anodizing or chemical conversion treatment on the pure metal layer and a part of the alloy member underneath, to obtain a coating laminate structure comprising the alloy member and a coating formed on the surface of the alloy member, A method for manufacturing a coating laminate structure, wherein a crystallized phase of the silicon or Ca-Al-based additive contained in the alloy member is present at an interface between the alloy member and the coating in the coating laminate structure, the interface is linear in a cross section of the coating laminate structure except for a portion where the crystallized phase is present, and the portion where the crystallized phase is present is uneven.

2. 2. The method for manufacturing a film laminate structure according to claim 1, wherein the anodizing treatment is performed by direct current electrolysis, a constant current is applied, and the anodizing treatment is terminated at or after the rate of increase in voltage with respect to reaction time increases.

3. 2. The method for manufacturing a film laminate structure according to claim 1, wherein the anodizing treatment is performed by AC-DC superimposed electrolysis, the voltage is kept constant, and the anodizing treatment is terminated at or after the point at which the rate of decrease in current with respect to reaction time increases.

4. The method for producing a coating laminate structure according to claim 1 , wherein the chemical conversion treatment is terminated at or after a time when the reaction with the pure metal layer by the chemical conversion treatment has ended.

Citation Information

Patent Citations

  • Aluminum alloy painted plate for outside plate of automobile

    JP1987180096A

  • Aluminum plated substrate for anodic oxidation

    JP1990057690A

  • Aluminum composite member

    JP2000313996A

  • Anodized film and anodizing method

    JP2006083467A

  • Method for manufacturing piston for direct injection engine

    JP2016037660A